Some Questions Regarding the State of Emergency - Dacar, Rok (65 pravne znanosti v Mariboru, 2026)
This chapter of the monograph analyses the legal concept of the state of emergency as a special constitutional regime that allows temporary derogations from the ordinary legal guarantees in the event of major crises. It analyses the historical development and different legal frameworks in selected European countries and then focuses on the state of emergency in the Republic of Slovenia. Particular attention is paid to the distinction between emergencies and states of emergency, the inconsistencies in legal terminology, the procedures for declaring a state of emergency and its impact on human rights and the balance of powers. The chapter highlights the risks of executive overreach and emphasizes the need for legal clarity, proportionality of measures and compliance with constitutional and international standards. It concludes that even in exceptional circumstances, the legal system must ensure safeguards against abuses and uphold the rule of law and democratic accountability.